Extensive Communications for Increasing Community Awareness in Handling Waste (Disposable Diapers): A Bibliometric Study - Adinda Rachmanillah; Totok Wahyu Abadi; Poppy Febriana; Muhammad Andi Fikri; Nur Maghfira Aesthetika; Muhammad Yani (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
In the disposal of urban and rural garbage, diaper waste has emerged as a new phenomenon. If this kind of waste is put into a river, it will harm the water environment because the earth cannot quickly break down it. This study aims to clarify the efficacy of counseling communication in raising public knowledge of postal waste management (disposable diapers). Bibliometric analysis is used in this quantitative descriptive study. The objective is to get fresh data on the investigation of extension communication to raise public knowledge of the disposal of pospak waste. Google Scholar and Crossref, two publisher sources, were used to gather the data. Through Publish or Perish, you can access articles from both sources. After gathering the data, VOS viewer is used to analyzing it. The results of the study indicate that counseling information is still an exciting topic in increasing public awareness. The importance of communication in handling waste is included in cluster 5. While public awareness in handling waste is included in cluster 3. The study of "Waste Management" is a point of attention of researchers which can be found in 8 clusters on research topics.